Socrative, Quizizz, and Google Form as Online-Based Evaluation Tools for Maharah Al-Qirā'ah Learning - Ali Mufti; Maksudin Maksudin; R Umi Baroroh; Agung Setiyawan (Maharaat: Jurnal Pendidikan Bahasa Arab, 2022)
The use of technology to innovate in learning methods and media has been widely carried out, including in the learning process of the Al-Qirā'ah Al-Asāsiyyah course at the Arabic Language Education Study Program at UIN Sunan Kalijaga Yogyakarta in the third semester. The purpose of this study is to describe students' perspectives on the advantages and challenges of using online-based evaluation tools: Socrative, Quizizz, and Google Form in the learning process at Al-Qirā'ah Al-Asāsiyyah courses. This study is a descriptive quantitative research that uses a questionnaire to collect data. This study revealed several advantages of using the online-based evaluation tools, such as being easy to use, effective, and can motivate students. Meanwhile, the challenges that must be faced are students must be connected to the internet network, the lack of variety in Arabic fonts, and the lack of variety in types of questions. Among the three types of evaluation tools offered, students prefer Quizizz over others.